2020
DOI: 10.1111/anec.12760
|View full text |Cite
|
Sign up to set email alerts
|

Assessing heart rate variability in type 1 diabetes mellitus—Psychosocial stress a possible confounder

Abstract: Background Autonomic neuropathy (AN) commonly arises as a long‐term complication in diabetes mellitus and can be diagnosed from heart rate variability (HRV), calculated from electrocardiogram recordings. Psychosocial stress also affects HRV and could be one of several confounders for cardiac AN. The present work investigated the impact of psychosocial stress on HRV in individuals with type 1 diabetes mellitus (T1DM) and assessed the use of salivary cortisol as a biomarker for psychosocial stress in this contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Assessment of heart rate variability (HRV) has received attention as a non-invasive subclinical method to assess autonomic regulation in individuals with type 1 diabetes. [1][2][3] Vinik et al 4 showed that chronically reduced HRV is associated with increased risk of arrhythmia, myocardial infarction, sudden cardiac death and cardiac autonomic neuropathy in people with type 1 and type 2 diabetes. Impaired cardiac autonomic modulation is a progressive phenomenon that is associated with hypoglycaemia and overall glycaemic control, however, the mechanisms behind the development of this alteration are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of heart rate variability (HRV) has received attention as a non-invasive subclinical method to assess autonomic regulation in individuals with type 1 diabetes. [1][2][3] Vinik et al 4 showed that chronically reduced HRV is associated with increased risk of arrhythmia, myocardial infarction, sudden cardiac death and cardiac autonomic neuropathy in people with type 1 and type 2 diabetes. Impaired cardiac autonomic modulation is a progressive phenomenon that is associated with hypoglycaemia and overall glycaemic control, however, the mechanisms behind the development of this alteration are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of heart rate variability (HRV) has received attention as a non‐invasive subclinical method to assess autonomic regulation in individuals with type 1 diabetes 1–3 . Vinik et al 4 showed that chronically reduced HRV is associated with increased risk of arrhythmia, myocardial infarction, sudden cardiac death and cardiac autonomic neuropathy in people with type 1 and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, insulin resistance was shown to be associated with lower cardiac output [ 90 ] and cardiovascular suppression [ 91 ] during and after exercise or cardiac autonomic reflex tests. Anxiety [ 92 ] and psychosocial stress [ 93 ] were shown to reduce HRV and induce further parasympathetic suppression in persons with T1D, indicating the need to consider confounding factors in assessing CAN. Gender and race were also found to be associated with autonomic function [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…The many features of the selected studies are shown in Table 1. The participants in the studies selected were type I diabetes mellitus (T1DM) patients [55][56][57][58], T2DM patients [55,[58][59][60][61][62][63][64][65], pregnant women with gestational diabetes mellitus (GDM) [66][67][68], and patients with diabetic retinopathy (DR) [55]. Figure 1 shows the sample characteristics and psychometric or clinical instruments used to analyse the psychological alterations and primary outcomes related to the salivary biomarkers and psychological alterations.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 14 articles were included who fulfilled the inclusion criteria. Of these, 11 were observational analyses of which 4 were cross-sectional analyses [57,59,64,67] and 7 were longitudinal [55,56,[61][62][63]66,68]. In addition, three were experimental articles.…”
Section: Design Of the Studies Type Of Dm And Salivary Biomarkersmentioning
confidence: 99%